Management of Pediatric Nonepileptic Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The neurologist's and child psychiatrist's perspectives of the diagnosis and treatment of pediatric nonepileptic seizures (NES) were discussed at a multidisciplinary workshop sponsored by the National Institutes of Neurological Disorders and Stroke and of Mental Health, and the American Epilepsy Society, May 2005.